Invasive assessment of the coronary microcirculation using the index of microcirculatory resistance - Fiarresga, António (2014)
INTRODUCTION: The index of microcirculatory resistance (IMR) enables/provides quantitative, invasive, and real-time assessment of coronary microcirculation status. AIMS: The primary aim of this study was to validate the assessment of IMR in a large animal model, and the secondary aim was to compare two doses of intracoronary papaverine, 5 and 10 mg, for induction of maximal hyperemia and its evolution over time. METHODS: Measurements of IMR were performed in eight pigs. Mean distal pressure (Pd) and mean transit time (Tmn) were measured at rest and at maximal hyperemia induced with intracoronary papaverine, 5 and 10 mg, and after 2, 5, 8 and 10 minutes. Disruption of the microcirculation was achieved by selective injection of 40-μm microspheres via a microcatheter in the left anterior descending artery. RESULTS: In each animal 14 IMR measurements were made. There were no differences between the two doses of papaverine regarding Pd response and IMR values - 11 ± 4.5 U with 5 mg and 10.6 ± 3 U with 10 mg (p=0.612). The evolution of IMR over time was also similar with the two doses, with significant differences from resting values disappearing after five minutes of intracoronary papaverine administration. IMR increased with disrupted microcirculation in all animals (41 ± 16 U, p=0.001). CONCLUSIONS: IMR provides invasive and real-time assessment of coronary microcirculation. Disruption of the microvascular bed is associated with a significant increase in IMR. A 5-mg dose of intracoronary papaverine is as effective as a 10-mg dose in inducing maximal hyperemia. After five minutes of papaverine administration there is no significant difference from resting hemodynamic status.